Clinical management of a ruptured intracranial aneurysm - Trakolis, Leonidas; Petridis, Athanasios K. (Frontiers in Stroke, 2024)
Background Intracranial hemorrhage due to a ruptured aneurysm is one of the most serious neurosurgical emergencies. The patient mostly presents with severe headaches and neurological deterioration. A rapid diagnosis and an interdisciplinary approach play a major role in the fate of these patients. The treatment can vary from endovascular to surgical and must be carefully and individually planned. Neurovascular expertise and an interdisciplinary approach are of vital importance and obligatory for the best possible outcome. Methods In this narrative review, we scrutinize the current literature and discuss the actual data and guidelines in order to emphasize the importance of the interdisciplinary expertise and approach in patients with ruptured intracranial aneurysm. Results The current approach to patients with ruptured aneurysm is inhomogeneous and often ineffective due to internal disputes between different disciplines. Although there is plenty of literature and hard evidence to “show the way,” many still choose to base their decisions on personal experience or opinion. Conclusions Every ruptured brain aneurysm should be approached in an interdisciplinary manor and treated according to the current evidence and guidelines.